2000
DOI: 10.1002/(sici)1097-4628(20000725)77:4<914::aid-app27>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Studies of crosslinked styrene-alkyl acrylate copolymers for oil absorbency application. II. Effects of polymerization conditions on oil absorbency

Abstract: ABSTRACT:Crosslinked styrene-acrylate copolymers were synthesized and evaluated by swelling properties for oil-absorbency application. The effect of various polymerization conditions (crosslinking agent concentration, initiator concentration, monomer concentration, and polymerization temperature) were studied through oil-absorption tests using kerosene oil. The oil absorbency was influenced mainly by the degree of crosslinking and the hydrophobicity of the copolymer units. The effect of moisture and the types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 5 publications
0
59
0
Order By: Relevance
“…Among them, oil-absorbent is widely regarded as the best cleanup material for absorbing oils because of the relatively fast oil absorption rate, large oil absorbency, and good absorption selectivity of oil over water. Many researchers have made significant contributions towards the progress on the synthesis of oil-absorbent (Farag & El-Saeed, 2008;Jang & Kim, 2000a, 2000bKim, Chung, Ha, Kim, & Cho, 1999;Medeiros, Oliveira, Sansiviero, Araujo, & Lago, 2010;Shan, Xu, Weng, & Huang, 2003a, 2003bShimizu, Koshiro, Yamada, & Tada, 1997;Zhou & Chuai, 2010). Atta and coworkers reported some oil-absorbents based on polyisobutylene/octadecyl acrylate copolymers (Atta, El-Ghazawy, Farag, & Abdel-Azim, 2006), cinnamoyloxyethyl methacrylates/isooctyl acrylate (Atta, El-Ghazawy, Farag, ElKafrawy, & Abdel-Azim, 2005), and reactive ␣-olefins/maleic anhydride (Atta & Arndt, 2005;Atta, El-Hamouly, Sabagh, Al, & Gabr, 2007a, 2007b.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Among them, oil-absorbent is widely regarded as the best cleanup material for absorbing oils because of the relatively fast oil absorption rate, large oil absorbency, and good absorption selectivity of oil over water. Many researchers have made significant contributions towards the progress on the synthesis of oil-absorbent (Farag & El-Saeed, 2008;Jang & Kim, 2000a, 2000bKim, Chung, Ha, Kim, & Cho, 1999;Medeiros, Oliveira, Sansiviero, Araujo, & Lago, 2010;Shan, Xu, Weng, & Huang, 2003a, 2003bShimizu, Koshiro, Yamada, & Tada, 1997;Zhou & Chuai, 2010). Atta and coworkers reported some oil-absorbents based on polyisobutylene/octadecyl acrylate copolymers (Atta, El-Ghazawy, Farag, & Abdel-Azim, 2006), cinnamoyloxyethyl methacrylates/isooctyl acrylate (Atta, El-Ghazawy, Farag, ElKafrawy, & Abdel-Azim, 2005), and reactive ␣-olefins/maleic anhydride (Atta & Arndt, 2005;Atta, El-Hamouly, Sabagh, Al, & Gabr, 2007a, 2007b.…”
Section: Introductionmentioning
confidence: 90%
“…However, when the amount of ␤-CD-A exceeds 7 wt%, the oil absorbency decreases to different extents in all the four oils. It is well known that an excess of cross-linking agent will cause the formation of a too denser network of the copolymer and reduce drastically the chain length between cross-linking points, meanwhile causing an excessive decrease in the mobility of the polymeric chains (Atta et al, 2006;Jang & Kim, 2000b;Shan et al, 2003b). This is disadvantageous for the oil to flow inside the network of the absorbent and accordingly the oil absorbency is low.…”
Section: Effect Of Cross-linking Agent Content On Oil Absorbencymentioning
confidence: 99%
“…Moreover, PBMA shown in Table 2 and PBMA/HEMA in our pervious studies [19] have hardly swollen in kerosene. It is reported that the number of carbon in alkyl groups of the copolymer is larger than the number of carbon in oil molecular, higher absorbency will be expected [4]. As we know, kerosene is a mixture of carbon chains that typically contain between 6 and 16 carbon atoms per molecule.…”
Section: Resultsmentioning
confidence: 99%
“…As a novel class of absorbents, alkyl acrylate copolymers [2,3], which have hydrophobicity, lipophilic, and gel-type structure consisting of a 3-D elastic network, make them excellent candidates for oil absorption. Jang and Kim [4] have reported maximum capacity of alkyl acrylate copolymers about 15 g/g. Recently, Ceylan and his co-workers [5] attained butyl rubber (BR); the sorption capacity of BR for crude oil and petroleum products is 15-23 g/g.…”
Section: Introductionmentioning
confidence: 99%
“…Kim and coworkers concluded that oil absorbency is influenced mainly by the degree of the crosslinking and the hydrophobicity of the copolymer units; the copolymer with the longer acrylate chain displays higher oil absorbency. 31,32 Recently, we synthesized crosslinked poly(orthocarbonate)s based on tetraethyl orthocarbonate for organic solvent absorption. 33 All synthesized poly(orthocarbonate)s are thermally stable and have very fast and very good solvent uptake abilities.…”
Section: Introductionmentioning
confidence: 99%